A NATIONAL-WIDE SURVEY OF TOBACCO CONTROL CURRICULA IN MEDICAL SCHOOLS - Ravara, Sofia Belo (2018)
Aim: To explore attitudes/knowledge, perceptions of curricula contents and confidence / competence to intervene in tobacco cessation/prevention among finalists medical students in Portugal. Methods: In 2016, a national cross-sectional study was carried out using a multiple-dimension questionnaire administered online/classroom. Results: Participants: 452 (24.2% of finalists), 72.1% females, age mode 23 years. Cronbach’s alfa analysis was reliable. While most students reported good knowledge about tobacco hazards, positive attitudes regarding their role in supporting cessation and their need for training; a significant part disagreed that they should be role models and that their behaviour would influence cessation outcomes; denying that curricula impacts in their attitudes. While most students reported receiving good theoretical training, particularly in tobacco hazards, a significant part considered their training poor, respectively in behaviour change and brief cessation skills: 38.4% reported low self-competence to intervene. From a 1-10 scale, mean score of self-confidence to intervene in cessation was 5.5. This was significantly associated with tobacco behaviour, SHS exposure, attitudes/knowledge, perception of theoretical training, and, above all, clinical skills training and tobacco curricula extension (mean:3 hours). Students considered their training insufficient and provided clear indications about curricula gaps (contents/format). Conclusions: There is room for improving undergraduate medical education in tobacco control, including the hidden curriculum. A national-wide assessment involving students is a key step to engage decision makers and stress the need for curriculum and organizational change.